2019
DOI: 10.1002/mp.13774
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Characterization of x‐ray beam profiles for a fluoroscopic system incorporating copper filtration

Abstract: Purpose The goal of this study was to investigate x‐ray beam profiles at various water depths to characterize the two‐dimensional x‐ray dose distribution, allowing for off‐axis and out‐of‐field radiation dose estimation for a wide range of x‐ray beam spectra commonly encountered in fluoroscopically guided interventional procedures. Methods A Siemens Artis interventional fluoroscope was operated in a service mode to generate a continuous x‐ray beam at fixed x‐ray beam spectra, defined by their kVp and the thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…This additional uncertainty was estimated in a previous study (7) to be 5% for beam spectra commonly encountered during adult fluoroscopic imaging, but this uncertainty may vary by as much as 12% for beam spectra commonly encountered during pediatric imaging when using a correction factor derived from the American Association of Physicists in Medicine Task Group 190-recommended beam spectra (90-100 kV without a prescribed amount of additional filtration). Second, there are substantial variations in X-ray beam quality and intensity across the X-ray field because of the anode heel effect; with dependencies on X-ray beam quality and field size, variations at or near the skin entrance can exceed ±20% from central axis measurements (15,16). Application of these uncertainties and specific approaches to estimating PSD are beyond the scope of this work; however, valuable discussions regarding approaches to PSD calculations have been published previously (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…This additional uncertainty was estimated in a previous study (7) to be 5% for beam spectra commonly encountered during adult fluoroscopic imaging, but this uncertainty may vary by as much as 12% for beam spectra commonly encountered during pediatric imaging when using a correction factor derived from the American Association of Physicists in Medicine Task Group 190-recommended beam spectra (90-100 kV without a prescribed amount of additional filtration). Second, there are substantial variations in X-ray beam quality and intensity across the X-ray field because of the anode heel effect; with dependencies on X-ray beam quality and field size, variations at or near the skin entrance can exceed ±20% from central axis measurements (15,16). Application of these uncertainties and specific approaches to estimating PSD are beyond the scope of this work; however, valuable discussions regarding approaches to PSD calculations have been published previously (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the same work reported that 20% of the primary beam intensity was found just outside the edge of the beam, with a decline to 3% at a position 6 cm from the edge. X‐ray beam intensity variations, due to the heel effect, field size, tube voltage and spectral filtration, are important for backscatter corrections in PSD estimation in FGI procedures with overlapping fields 41,42 …”
Section: Current and Emerging Methods To Estimate Patient Skin Dosementioning
confidence: 99%
“…X-ray beam intensity variations, due to the heel effect, field size, tube voltage and spectral filtration, are important for backscatter corrections in PSD estimation in FGI procedures with overlapping fields. 41,42 To illustrate the variability and dependencies of backscatter factors, Fig. 6 shows the ratio of exposure from a 6 cm 2 × 6 cm 2 X-ray beam measured with an ionization chamber on the entrance surface of a number of different phantoms, compared to that of a 30 cm 3 × 30 cm 3 × 20 cm 3 block of solid water.…”
Section: A1 the Backscatter Factormentioning
confidence: 99%
See 2 more Smart Citations